Understanding the impact of Fused Filament Fabrication conditions on the microstructure and tensile properties of polyamide 6 by thermal and optical live monitoring. (September 2021) - Sgrulletti, Matteo; Bragaglia, Mario; Giarnetti, Sabino; Paleari, Lorenzo; Nanni, Francesca
Abstract: Commercially available FFF machines have limitations in process reliability and quality of the products. The live monitoring of the 3D printing process could improve quality and the produced part performance. In the present work, a print-head integrated system, based on optical and thermal sensors, for live monitoring of a FFF 3D printing process was developed. A Design of Experiments (DoE) campaign has been set in order to optimize the printing process parameters for polyamide 6 (PA6), starting from the analysis of the acquired data. Experimental results show that optical and thermal cameras allow to detect invisible to naked eye defects, such as warping, incorrect filament deposition, stringing and oozing. Moreover, the thermal data have been successfully used to calculate the cooling kinetics of the different layers of a job, providing direct information related to degree of crystallinity. From DoE campaign the bed temperature has been found to be the most influential process parameter affecting morphology and mechanical properties of 3D printed samples. Optimized samples show an increase of young modulus and tensile strength up to 70% and 79% respectively compared to not optimized samples. Graphical Abstract: ga1 Highlights: A print-head integrated system was developed for live monitoring of FFF 3D printing of PA6. Optical and thermal cameras allow for identification of invisible to naked-eye printing defects. IR camera allows for the determination of cooling rate of the material during 3D printing. From statistical analysis, bed temperature is the most influent process parameter for dimensional accuracy and mechanical properties.